Место теологии в светском литературном памятнике (теологические изыскания Страбона) - Грацианская, Л.И. (Боспорские исследования, 2009)
Divine power ran through all spheres of life of ancient Greeks and Romans during the existence of antiquity. Concrete manifestations of ancient religious mentality and ritual were diverse and varied diachronically both in geographical and social spaces. Rationalistic explanation of mythology creation and the myths correspondingly runs through all «Geography» of Strabo. The ancient author mentions educative role of myths. Strabo discusses the role of myths in the process of upbringing concrete human’s morality and their benefit for the state. He strongly objects the idea of passing anything mythological off as History Rationalistic explanation of mythology relying to religious and cult plots as well as historical rationalistic survey of many religious and cult phenomena is extremely peculiar to him.